(untitled) (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-2-129-139 The article discusses the evolution of R. P. Kumov, one of the largest Don writers of the Silver Age, perceived by modern critics as the "Don Chekhov". This was facilitated by the lyrical beginning of his style, subtle psychologism in the depiction of characters, for the most part people of the clergy – from a novice to a bishop. At the beginning of his career, he openly focuses on the plots of Chekhov’s famous works, uses the techniques of his poetics, creating a kind of literary palimpsest. But already in the first half of the 1910s, new themes, characters, motives appeared in his prose and especially in dramaturgy, the desire to depict acute conflicts of our time, large and controversial characters. After 1917, he became a witness and artistic chronicler of the Don Vendee, a fratricidal civil war on the Don. Cossack folklore, motifs and images of folk eschatology play a significant role in his Don texts. All this indicates the need to revise the established ideas about the literary attribution of the writer and his place in Russian literature of the 20th century. The lyrical "mood" as the dominant beginning of his poetics, landscape painting are in many ways related to the aesthetics of Russian impressionism (B. Zaitsev, I. Shmelev, S.N. Sergeev-Tsensky). It is no coincidence that the writer especially singled out S.N. Sergeev-Tsensky. However, this aspect of Kumov’s poetics requires special study. Kumov’s artistic method cannot be reduced to a single formula. A systematic approach is required to the problem of the evolution of his work, in which romance and realism, spiritual and religious, and psychological, Don and all-Russian, "native and universal" turned out to be inseparable. The definition of the "Don Chekhov" reflects only one of the features of his artistic manner, which is very important, but not accurate enough for literary attribution of the writer’s work. Key words: R. P. Kumov, A. P. Chekhov, literary palimpsest, spiritual prose, dramaturgy, Don literature